2017
DOI: 10.1038/cdd.2016.162
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 mediates transmembrane TNF-alpha-induced formation of death-inducing signaling complex and apoptotic signaling via TNFR1

Abstract: Tumor necrosis factor-alpha (TNF-α) exists in two forms: secretory TNF-α (sTNF-α) and transmembrane TNF-α (tmTNF-α). Although both forms of TNF-α induce tumor cell apoptosis, tmTNF-α is able to kill tumor cells that are resistant to sTNF-α-mediated cytotoxicity, indicating their differences in signal transduction. Here, we demonstrate that internalization of TNFR1 is crucial for sTNF-α- but not for tmTNF-α-induced apoptosis. sTNF-α induces binding of tumor necrosis factor receptor type 1-associated death domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 36 publications
0
41
0
1
Order By: Relevance
“…Similarly, both TNF receptors are TACE substrates 38 . In addition, transmembrane TNF induces the formation of STAT1-dependent death-inducing signaling complexes (DISC) and apoptosis through its interaction with TNFR1 39 . These data suggest that MCJ deficiency contributes to disease severity at least partly due to the regulation of membrane TNF and its ability to signal through TNFR1.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, both TNF receptors are TACE substrates 38 . In addition, transmembrane TNF induces the formation of STAT1-dependent death-inducing signaling complexes (DISC) and apoptosis through its interaction with TNFR1 39 . These data suggest that MCJ deficiency contributes to disease severity at least partly due to the regulation of membrane TNF and its ability to signal through TNFR1.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al previously reported that STAT1 can directly interact with TNFR1 and TRADD, as a component of the TNF-α receptor 1-TRADD signaling complex, to inhibit NF-κB activation ( 51 ). Jiang et al recently reported that the phosphorylation of STAT1 enhanced its binding to TRADD and thus recruits FADD and caspase 8 to form DISC complexes, resulting in apoptosis but not NF-κB activation ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…If NFκB activation is impaired, FADD and procaspase 8 attach to TNFR1-associated complex 1. As a result, caspase-8 is activated through limited proteolysis, and the process of apoptosis begins [20,21].…”
Section: Mitochondrial Pathwaymentioning
confidence: 99%